Undergraduate Student Attitudes and Perspectives of the Accessibility, Supportiveness, and Appreciation of Research Opportunities in the Health Sciences - Luo, Owen Dan; Lin, Sabrina H.; Grover, Sanya; Sritharan, Praveen; Hansen, Stine (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
Undergraduate research is a “high-impact” educational practice that enriches student learning and facilitates student career advancement. This sequential explanatory mixed methods study, composed of a quantitative online questionnaire followed by qualitative focus group interviews, sought to explore undergraduate student attitudes on research and elicit perceived facilitators and barriers to undergraduate research engagement. The survey respondents (N = 377), all undergraduate health sciences students at McMaster University in Hamilton, Ontario, generally had positive attitudes toward undergraduate research, but had polarized perceptions of its accessibility, supportiveness, and appreciation. Follow-up focus group interviews with selected participants (N = 11) revealed four main themes: (1) the hidden curriculum of undergraduate research, (2) the paucity of meaningful research work for emerging student researchers, (3) the administrative barriers within the undergraduate research landscape, and (4) the inequitable access to undergraduate research opportunities. This study’s findings suggest potential avenues to improve the undergraduate student research experience.